PREDIKSI JUMLAH PENDAFTARAN SISWA BARU DENGAN METODE TIME SERIES - Yulistika Handini; Jusuf Wahyudi; Jhoanne Fredricka (Smart Education, 2024)
Abstract: North Bengkulu State Vocational School 2 is one of the Vocational High Schools in North Bengkulu which has several majors that students can choose from. At the beginning of each new academic year, there will be a reception for prospective new students. There is often competition in attracting prospective new students to enter SMK Negri 2 North Bengkulu. With competition between vocational schools, the number of new student registrations will increase each year and it is possible that there will be a decrease in prospective new students, so that the number of new students at these vocational schools will be unstable. The prediction application for the number of new student registrations at SMK Negeri 2 North Bengkulu is an application that can help schools find out how many student registrations there will be in the next/next academic year based on the results of analysis that has been carried out from previous trend data. From the results of the time series method analysis, the predicted results for the number of new student enrollments in the 2023/2024 academic year were obtained, namely TKRO of 99.4937 students, TKP of 36.0888 students, and TKJ of 64.0501 students Keywords: prediction; number of new student registrations; time series method Abstrak: SMK Negeri 2 Bengkulu Utara merupakan salah satu Sekolah Menengah Kejuruan yang terdapat di Bengkulu Utara yang memiliki beberapa jurusan yang dapat dipilih oleh siswa/i. Setiap awal tahun ajaran baru akan menyelenggarakan penerimaan calon peserta didik baru. Sering terjadi persaingan dalam menarik minat calon siswa baru untuk masuk SMK Negri 2 Bengkulu Utara. Dengan adanya persaingan antar SMK, jumlah pendaftaran siswa baru setiap tahunnya akan mengalami peningkatan dan tidak menutup kemungkinan akan mengalami penurunan calon peserta didik baru, sehingga jumlah siswa baru di SMK tersebut tidak stabil. Aplikasi prediksi jumlah pendaftaran siswa baru di SMK Negeri 2 Bengkulu Utara merupakan suatu aplikasi yang dapat membantu sekolah dalam mengetahui berapa banyak jumlah pendaftaran siswa/i di tahun ajaran mendatang/berikutnya berdasarkan hasil analisis yang telah dilakukan dari data trend sebelumnya. Dari hasil analisis metode time series, diperoleh hasil prediksi jumlah pendaftaran siswa baru pada Tahun Ajaran 2023/2024 yaitu TKRO sebanyak 99,4937 siswa/i, TKP sebanyak 36,0888 siswa/i, dan TKJ sebanyak 64,0501 siswa/i Kata kunci: prediksi; jumlah pendaftaran siswa baru; metode time series